Hepatitis C in 2020: A North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition Position Paper. Issue 3 (September 2020) - Leung, Daniel H.; Squires, James E.; Jhaveri, Ravi; Kerkar, Nanda; Lin, Chuan-Hao; Mohan, Parvathi; Murray, Karen F.; Gonzalez-Peralta, Regino P.; Roberts, Eve A.; Sundaram, Shikha S.
Abstract : ABSTRACT: In 1989, a collaboration between the Centers for Disease Control (CDC) and a California biotechnology company identified the hepatitis C virus (HCV, formerly known as non-A, non-B hepatitis virus) as the causative agent in the epidemic of silent posttransfusion hepatitis resulting in cirrhosis. We now know that, the HCV genome is a 9.6 kb positive, single-stranded RNA. A single open reading frame encodes a 3011 amino acid residue polyprotein that undergoes proteolysis to yield 10 individual gene products, consisting of 3 structural proteins (core and envelope glycoproteins E1 and E2) and 7 nonstructural (NS) proteins (p7, NS2, NS3, NS4A, NS4B, NS5A, and NS5B), which participate in posttranslational proteolytic processing and replication of HCV genetic material. Less than 25 years later, a new class of medications, known as direct-acting antivirals (DAAs) which target these proteins, were introduced to treat HCV infection. These highly effective antiviral agents are now approved for use in children as young as 3 years of age and have demonstrated sustained virologic responses exceeding 90% in most genotypes. Although tremendous scientific progress has been made, the incidence of acute HCV infections has increased by 4-fold since 2005, compounded in the last decade by a surge in opioid and intravenous drug use. Unfortunately, awareness of this deadly hepatotropic virus among members of the lay public remains limited. Patient education, advocacy, and counseling must, therefore, complement the availability of curative treatments against HCV infection if this virus is to be eradicated. Abstract : Supplemental Digital Content is available in the text